Transfer arystokracji a ewolucja śląskiego "herrenstand" w pierwszej połowie XVIII w. = Transfer of aristocracy and the evolution of the Silesian "herrenstand" in the first half of the 18th century - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The transfer of upper-class culture into Silesia in the first decades of the 18th century followed the awards of nobility and grants of land by the emperor. That long-term process, that was started as early as in the first decades of the 17th century, gathered momenturn after the Czech opposition had been crushed in 1620 and got even stronger with the establishment of the "Supervisory Agency" (Oberamt) in Breslau in 1629, which manifested the emperor's strife for absolute power.
Keywords: Śląsk - 18 w.; arystokracja